2020
DOI: 10.2147/cmar.s276286
|View full text |Cite
|
Sign up to set email alerts
|

<p>Synchronous Metastatic Nasopharyngeal Carcinoma: Characteristics and Survival of Patients Adding Definitive Nasopharyngeal-Neck Radiotherapy to Systematic Chemotherapy</p>

Abstract: To determine the M1 sub-staging in synchronous metastatic nasopharyngeal carcinoma (smNPC) and to examine the effect of nasopharyngeal-neck radiotherapy (RT) and local treatment of metastases on overall survival (OS) of smNPC patients. Patients and Methods: A total of 150 patients with smNPC were included. Metastatic characteristics associated with their potential prognostic significance were analyzed. Then, a stratification system of the M1 sub-staging in smNPC was provided according to metastatic features. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
(35 reference statements)
3
9
0
Order By: Relevance
“…Retrospective data, including ours, have suggested a role of LRRT in de novo mNPC based on conventional radiotherapy 16‐21 . This phenomenon was further confirmed in the subsequent IMRT era 7‐10,22,23 . Liao et al 8 conducted a retrospective study of 150 synchronous mNPC patients and indicated that LRRT plus PCT significantly improved OS compared to PCT alone (median OS, 34.0 vs. 15.2 months, 3‐year OS 44.9% vs. 24.8%, p = 0.002).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Retrospective data, including ours, have suggested a role of LRRT in de novo mNPC based on conventional radiotherapy 16‐21 . This phenomenon was further confirmed in the subsequent IMRT era 7‐10,22,23 . Liao et al 8 conducted a retrospective study of 150 synchronous mNPC patients and indicated that LRRT plus PCT significantly improved OS compared to PCT alone (median OS, 34.0 vs. 15.2 months, 3‐year OS 44.9% vs. 24.8%, p = 0.002).…”
Section: Discussionsupporting
confidence: 61%
“…As have been recommended in current National Comprehensive Cancer Network (NCCN) and European Society for Medical Oncology (ESMO) guidelines, palliative chemotherapy (PCT) (i.e., platinum‐based combination regimens) is commonly used as a first‐line therapy since platinum represents the most effective agent 1,2 . However, reported survival outcomes of de novo mNPC treated by PCT alone were far from satisfactory, with the indicated median overall survival (OS) time ranging from 12 to 21 months 3‐9 . Thus, how to improve the survival further in this subgroup of patients remains an urgent issue to be clarified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rusthoven et al reported that compared to chemotherapy alone, local radiotherapy combined with chemotherapy was associated with improved OS (median OS 21.4 vs 15.5 months, 5-year OS 28% vs 10%), resulting in a 39% reduction of death risk [13]. Similar ndings were also found in some retrospective studies [14][15][16][17][18][19][20]. Up to now, there are only one multicenter phase 3 randomized clinical trial investigated the e cacy of LLRT in de novo mNPC.…”
Section: Discussionsupporting
confidence: 53%
“…Since there is no consensus on who should receive LLRT and / or RT to metastatic sizes after rst-line PCT, prognostic models and risk strati cations guiding the subdivisions of mNPC patients based on clinical features, therapeutic response and blood biomarkers had been widely researched to identify the optimal candidates [3,14,17,19,[22][23][24][25], as well as in mNPC with bone-only metastasis [6, 9-11, 21, 26].…”
Section: Discussionmentioning
confidence: 99%